Effects of Soil Pre-Treatment with Basamid® Granules, Brassica juncea, Raphanus sativus, and Tagetes patula on Bacterial and Fungal Communities at Two Apple Replant Disease Sites - Yim, Bunlong; Nitt, Heike; Wrede, Andreas; Jacquiod, Samuel; Sørensen, Søren J.; Winkelmann, Traud; Smalla, Kornelia (Frontiers in Microbiology, 2017)
Nurseries producing apple and rose rootstock plants, apple orchards as well as rose production often experience replanting problems after several cultivations on the same site when a chemical soil disinfectant is not applied. The etiology of apple and rose replanting problems is most likely caused by soil-borne pathogen complex, defined as ‘replant disease (RD)’. RD symptoms are typically reduced shoot and root growth, a smaller leaf area, a significant decrease in plant biomass, yield and fruit quality and a shorter life span. In our previous study, we showed that RD symptoms were reduced when apple rootstock M106 were grown in RD soils treated either with the soil fumigant Basamid or after biofumigation by incorporating Brassica juncea or Raphanus sativus or by growing Tagetes under field conditions compared to untreated control soil. The present study aimed at identifying potential bacterial and fungal taxa that were affected by different soil treatments and linking bacterial and fungal responders to plant performance. Miseq® Illumina® sequencing of 16S rRNA gene fragments (bacteria) and ITS regions (fungi) amplified from total community DNA extracted from soil samples taken four weeks after treatments were performed. Soil properties and culture history of the two RD sites influenced greatly soil microbiomes. Several bacterial genera were identified that significantly increased in treated soils such as Arthrobacter (R. sativus, both sites), Curtobacterium (Basamid, both sites), Terrimonas (Basamid and R. sativus, site A) and Ferruginibacter (B. juncea, site K and R. sativus, site A) that were also significantly and positively correlated with growth of apple M106 plants. Only few fungal genera, such as Podospora, Monographella and Mucor, were significantly promoted in soils treated with B. juncea and R. sativus (both sites). The least pronounced changes were recorded for bacterial as well as fungal communities in the RD soils planted with Tagetes. The detection of bacterial and fungal genera that were significantly increased in relative abundance in response to the treatments and that were positively correlated with plant growth suggests that management of the soil microbial community could contribute to overcome the apple RD encountered in affected sites.